Safety and efficacy of belt-type electrical stimulation for preventing disuse syndrome in elderly hemodialysis patients: a pilot study - Misa Miura; Shigeru Owada; Osamu Ito; Masahiro Kohzuki (Frontiers in Rehabilitation Sciences)
BackgroundElderly hemodialysis (HD) patients frequently experience reduced physical activity due to treatment-related immobility and fatigue, leading to accelerated functional decline. While exercise therapy is beneficial, adherence remains challenging among frail elderly patients. Belt-type electrical stimulation (B-SES) presents a potential alternative, though evidence for its safety and efficacy in this population is limited.MethodsIn this 12-week prospective intervention study, eight frail maintenance HD patients (mean age 75.5 ± 0.9 years) received B-SES therapy during HD sessions. Outcomes were assessed through physical function measures, biochemical markers, quality of life indices, and body composition analysis using multiple imaging modalities (BIA, CT, 1H-MRS).ResultsFive participants completed the intervention, with three withdrawals unrelated to the treatment. Physical function measures showed a trend toward improvement without elevation in inflammatory markers. While BIA showed no significant changes in muscle mass, CT analysis revealed increased thigh muscle cross-sectional area, and 1H-MRS indicated improvements in intramuscular fat composition. A significant correlation emerged between reduced intramyocellular lipids and improved physical performance measures (p < 0.05).ConclusionB-SES demonstrated safety and potential efficacy in improving physical function and muscle quality among frail elderly HD patients. From a public health perspective, B-SES may serve as a feasible and accessible intervention for this population, particularly in resource-limited settings. However, further studies are needed to determine its cost-effectiveness in comparison with conventional exercise therapy.